QUALIDADE DA ÁGUA SUBTERRÂNEA PARA CONSUMO HUMANO E USO AGRÍCOLA NO SUL DO ESTADO DO ESPÍRITO SANTO - Menezes, João Paulo Cunha; Bertossi, Ana Paula Almeida; Santos, Alexandre Rosa dos; Neves, Mirna Aparecida (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Water quality assessment is needed for ensure sustainable and safe use for drinking, farming and industrial purposes. The aim of this work was to analyze groundwater quality in the countryside of Alegre County, located in the Southern part of Espírito Santo State, which represents a typical example of small farms in the interior of Brazil. Standard methods of APHA were used to analyze water samples from 60 wells. Parameters that influence water quality for drinking and farming purposes were determined and compared with legal thresholds. Values of turbidity, pH, iron and thermo-tolerant coliforms were above permitted limits for drinking purposes of Brazilian Health Ministry´s regulation. It was not identified any problem in water quality for irrigation relating to salinity content, however, it is not recommended the use of this water for irrigation of vegetables that are raw consumed due the presence of thermo-tolerant coliforms.